Turkish parliamentary debates about the international recognition of the Armenian genocide: development and variations in the official denialism - Nefes, Türkay Salim; Gürpınar, Doğan; Kaymak, Özgür (Informa UK Limited, 2022)
The main source of animosity in modern Turkish – Armenian relations is the debate on the international recognition of the Armenian genocide. To provide an evidence-based and thorough perspective on the Turkish political stance in this discussion, this article explores all the relevant speeches in Turkish parliamentary records. It pays particular attention to political parties’ stances, the historical evolution of the debate, and the significance of the individual profiles of parliamentarians who contributed to the discussion. The findings show that most political parties in Turkey articulated versions of denial, except for a few marginal anti-denial voices. The study concludes that while political parties’ ideological orientations predominantly shape the Turkish debate on the international recognition of the Armenian genocide, historical contexts, local memories, and the individual backgrounds of parliamentarians seem to inspire minor variations in their tones.

© 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properlycited. The terms on which this article has been published allow the posting of the Accepted Manuscript in a repository by the author(s) orwith their consent.

The work was supported by the Fundação Calouste Gulbenkian [254570]

Peer reviewed
Keywords: Parliament; Armenian genocide; Turkey; Turkish nationalism; The armenian genocide; Denialism